Association between regional white and gray matter volume and ambiguity tolerance: Evidence from voxel‐based morphometry. (7th April 2015) - Tong, Dandan; Yang, Wenjing; Zhang, Qinglin; Li, Wenfu; Wei, Dongtao; Che, Xianwei; Zhang, Meng; Hitchman, Glenn; Qiu, Jiang; Liu, Yijun; Cao, Guikang
Abstract The concept of tolerance of ambiguity (AT) is defined as the way in which an individual tends to perceive and deal with confusing, vague, and unclear situations. AT is generally considered as an important personality trait, but the neural mechanisms underlying individual differences in AT have never been investigated. Using voxel‐based morphometry and MSTAT‐II scale, we investigated the correlations between AT and regional white matter volume (rWMV) and regional gray matter volume (rGMV) in 351 young healthy subjects. We found AT to be positively correlated with rGMV in the dorsolateral prefrontal cortex (DLPFC), and negatively correlated with rGMV in the precuneus. These results indicate that increased rGMV in the left DLPFC may lead to characteristics of ambiguous stimuli consideration from multiple contexts and risk taking. Decreased rGMV in the left precuneus may be associated with a high tolerance for ambiguity, which attributes uncertainty to self‐related factors.